Reprogrammable Materials: Magnetic Dynamic Polymers for Modular Assembling and Reconfigurable Morphing Architectures (Adv. Mater. 30/2021). Issue 30 (28th July 2021) - Kuang, Xiao; Wu, Shuai; Ze, Qiji; Yue, Liang; Jin, Yi; Montgomery, S. Macrae; Yang, Fengyuan; Qi, H. Jerry; Zhao, Ruike
Abstract : In article number 2102113, H. Jerry Qi, Ruike Zhao, and co‐workers report a novel magnetic dynamic polymer that consists of hard‐magnetic microparticles in a dynamic polymer network with thermally responsive reversible linkages. The polymer integrates functions including magnetic‐driven navigating, assembling, welding, morphing, reprogramming, and structural reconfiguration, providing a new paradigm for reprogrammable morphing architectures and devices.